2004
DOI: 10.1111/j.1365-2109.2004.01012.x
|View full text |Cite
|
Sign up to set email alerts
|

Dominant sources of dietary carbon and nitrogen for shrimp reared in extensive rice-shrimp ponds

Abstract: Stable isotope analysis was used to determine the sources of dietary nitrogen (N) and carbon (C) for shrimp during the rearing phase in extensive riceshrimp ponds in My Xuyen and Gia Rai districts,Vietnam. Farm-made feed was added as a food source in shrimp ponds in My Xuyen district, and based on stable isotope analyses, was generally a poor dietary source. The commercial formulated feed used in Gia Rai also appeared to contribute little directly to the nutritional needs of the shrimp. In contrast, the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Poor food availability and/or poor food quality can also affect shrimp survival and production. Our study showed that an indicator of food availability, Chl a (Burford et al., ,b), was positively correlated with production and survival, at least in 2014. This suggests that the natural food available in ponds may not have been sufficient to meet nutritional needs.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Poor food availability and/or poor food quality can also affect shrimp survival and production. Our study showed that an indicator of food availability, Chl a (Burford et al., ,b), was positively correlated with production and survival, at least in 2014. This suggests that the natural food available in ponds may not have been sufficient to meet nutritional needs.…”
Section: Discussionsupporting
confidence: 48%
“…This suggests that the natural food available in ponds may not have been sufficient to meet nutritional needs. Shrimp do not feed on water column algae, as measured by Chl a , but rather on microalgae growing on sediment and rice stubble, and fauna such as small crustaceans and molluscs (Burford et al., ). However, water column Chl a can provide an indicator of food availability, particularly as shrimp yield and survival also correlated with nutrient concentrations the same year they correlated with Chl a .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, mangrove leaf litter has a potential role in the food web of the shrimp ponds. A good practice for integrating shrimp culture in mangrove ecosystems should therefore include understanding the role of leaf litter in influencing the allochthonous and autochthonous organic inputs as sources of dietary carbon for shrimp (Burford et al 2004). Following leaf litter fall, the senescent mangrove leaves start to decompose through a considerable modification by bacteria and fungi and are utilized by epifauna ranging from direct shredders to primary and secondary consumers (Wilson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental studies of cultured aquatic species, isotopes of these elements are also the most commonly used, providing measures of energy transfer and protein utilization. In aquaculture pond systems, which represent semi-controlled aquatic mesocosms, both measurements of stable isotopes at natural abundance levels and isotopically-enriched nutritional substrates have been used to assess the sources and sinks for dietary carbon and nitrogen (Schroeder, 1983;Bombeo-Tuburan, et al, 1993;Nunes et al, 1997;Epp et al, 2002;Burford et al, 2004aBurford et al, , 2004b. Such studies have determined, for example, the flow of nutrients from feeds into sediments (Yokoyama et al, 2006), from feeds to microbial flocs (Burford et al, 2002), and the relative contribution of formulated feeds and natural productivity to tissue growth (Parker et al, 1989).…”
Section: Introductionmentioning
confidence: 99%